Electrically tunable liquid crystal optical microresonators - Humar, M; Ravnik, M; Pajk, S; Musevic, I (2009)
Because of their small mode volume and high Q-factors, optical microresonators are interesting for applications such as laser sources, active filters and all-optical switches. Especially interesting are tunable resonators, in which the resonance frequency tuning by size, shape, temperature or electric field can be achieved. Here we demonstrate electrically tunable, low-loss whispering-gallery-mode (WGM) resonators made of nematic liquid crystal droplets, embedded in a polymer matrix. The shift in resonant frequencies is achieved via electric field-induced structural distortion of the birefringent liquid crystal resonator medium. Nematic liquid crystal microresonators have a large tuning range of the order of 20nm at 2.6Vνm 1 for a 600nm WGM in 17-νm-diameter droplets and high Q-factors up to 12,000 in 33-νm-diameter droplets. The tunability is approximately two orders of magnitude larger than usually achieved in solid-state microresonators. © 2009 Macmillan Publishers Limited. All rights reserved.